Respuesta :
Answer:
[tex]\large\boxed{y=-\frac{3}{2}x+\frac{3}{2}}[/tex]
Step-by-step explanation:
Use the two-points slope equation: [tex]\boxed{m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}}[/tex]
Given the two coordinate points of [tex](x_{1}, y_{1})[/tex] and [tex](x_{2}, y_{2})[/tex], implement these values into the equation and solve for m.
[tex]m=\frac{(3)-(6)}{(-1)-(-3)}\\\\m=\frac{(-3)}{(2)}\\\\m=-\frac{3}{2}[/tex]
The slope is then placed in the equation - y = -3/2x + b.
Then, insert a value for y and x from the same coordinate point to solve for b.
[tex]6=-\frac{3}{2}(-3)+b\\\\6=\frac{9}{2}+b\\\\\frac{3}{2}=b[/tex]
Then, plug it all in to get [tex]\large\boxed{y=-\frac{3}{2}x+\frac{3}{2}}[/tex].
Answer:
y=-3/2x
Step-by-step explanation:
First, find the slope with y2-y1/x2-x1=m
3-6 m=-3/2
--------- =
-1-+-3
Now plug it in to point slope form
Point slope form is y-y1=m(x-x1)
y-3=-3/2(x--1) Distribute -3/2 to x and 1
y-3=-3/2x-3 Add three on both sides to get y alone
y=-3/2x Three's cancel out. This is the final equation.